Obinutuzumab is Effective as an Initial Treatment for PLA2R-Associated Primary Membranous Nephropathy: A Retrospective, Single-Center Trial - Li XQ; Liu Y; Cai ZY; Lv TG; Hao J (Drug Design, Development and Therapy)
Xue-Qi Li,1 Yang Liu,1 Ze-Yu Cai,1 Tie-Gang Lv,2 Jian Hao1 1Department of Medicine, Division of Nephrology, The Affiliated Hospital of Inner Mongolia Medical University, Hohhot, Inner Mongolia Autonomous Region, 010050, China; 2Department of Medicine, Division of Radiology, The Affiliated Hospital of Inner Mongolia Medical University, Hohhot, Inner Mongolia Autonomous Region, 010050, People’s Republic of ChinaCorrespondence: Jian Hao, Department of Medicine, Division of Nephrology, The Affiliated Hospital of Inner Mongolia Medical University, No. 1 North Passage Road, Huimin District, Hohhot, Inner Mongolia Autonomous Region, 010050, People’s Republic of China, Tel +8613704751021, Email jian_hao8865@126.comBackground: Membranous nephropathy (MN) can cause nephrotic syndrome. B cells contribute to MN, but available treatments are often inadequate. We addressed this treatment gap by analyzing the effect of obinutuzumab in patients with primary MN (PMN).Methods: Forty-seven PMN patients were followed for six months, with 25 receiving obinutuzumab and 22 (control) receiving rituximab. Treatment response was assessed by 24-h urine total protein (24-h UTP), serum albumin (ALB), and other indicators. Immunologic remission was assessed by measurement of anti-phospholipase A2 receptor autoantibodies (PLA2R autoAbs).Results: Relative to baseline, the obinutuzumab group had significant decreases of PLA2R autoAbs (83.40 [55.90– 344.36] vs 0.41 [0.17– 1.20] RU/mL), 24-h UTP (8.90 [7.15– 13.80) vs 1.82 [1.12– 3.43] g/day), and B cells (312.61 [202.00– 406.12) vs 0 [0– 0] cells/μL), and a significant increase of serum ALB (25.90 [20.85– 28.70] vs 42 [39.7– 45.3] g/L) after six months. Nineteen of the evaluable patients (76% [55– 91%]) achieved immunological remission at three months, 20 (80% [60– 93%] achieved immunological remission at six months, and 16 (64% [42– 83%] achieved partial response (PR) at three-months. After six-months, no patients achieved complete remission, but 19 (76% [55– 91%]) achieved PR. Before the second dose of obinutuzumab, the CD19+ B cell count in 20 patients (80%) [60%– 93%] was less than 1 cell/μL, and 18 patients had counts of 0 cells/μL. At the 6-month follow-up, the rituximab and obinutuzumab groups had no significant differences in immunological remission (80% vs 64%; OR: 2.29 [0.62– 8.47]; P=0.211) or clinical remission (76% vs 59%; OR: 2.19 [0.63– 7.66]; P=0.215]. No patients experienced serious adverse events.Conclusion: This retrospective analysis suggests that obinutuzumab may have potential as an initial therapeutic option for patients with PMN, although larger controlled studies are needed for confirmation.Keywords: obinutuzumab, PLA2R, membranous nephropathy, proteinuria